Sulfur-containing spiroketals from Breynia disticha and evaluations of their anti-inflammatory effect - Ken-ichi Nakashima; Naohito Abe; Masayoshi Oyama; Hiroko Murata; Makoto Inoue (Beilstein Journal of Organic Chemistry, 2023)
Breynia spp. are a key source of sulfur-containing spiroketal glycosides with potential anti-inflammatory activity. In this study, three new sulfur-containing spiroketals – breynin J (1), epibreynin J (2), and probreynogenin (3) – along with four known compounds – probreynin I (4), phyllaemblic acid (5), breynin B (6), and epibreynin B (7) – were isolated from the roots of Breynia disticha. The structures of compounds 1–7 were elucidated by extensive 1D and 2D NMR spectroscopic analyses, including 1D total correlation spectroscopy (TOCSY), HSQC, HMBC, double quantum-filtered (DQF)-COSY, heteronuclear two-bond correlation (H2BC), and HSQC-TOCSY experiments, as well as high-resolution electrospray ionization HRESIMS analysis, and quantum chemical electronic CD calculations. Furthermore, the absolute configurations of sugar residues were determined by derivatization of the hydrolysates with ʟ-cysteine methyl ester and o-tolyl isothiocyanate followed by HPLC analysis. The anti-inflammatory effects of the isolated compounds were evaluated based on the mRNA levels of proinflammatory cytokines in lipopolysaccharide (LPS)-stimulated RAW 264.7 murine macrophage cells. Compounds 1, 2, 6, and 7 inhibited the increase in interleukin (IL)-1β and IL-6 mRNA levels stimulated by LPS. Moreover, the most potent compound 7 was found to significantly inhibit the production of IL-1β and IL-6 proteins, as revealed by the analysis of culture supernatants.